An investigation of the perceived impact of the inclusion of steel pan ensembles in collegiate curricula in the Midwest - Yancey, Benjamin (Kansas State University, 2014)
The current study is an in depth look of the impact of steel pan ensemble within the college curriculum of the Midwest. The goal of the study is to further understand what perceived impacts steel pan ensemble might have on student learning through the perceptions of both instructors and students. The ensemble's impact on the students’ senses of rhythm, ability to listen and balance in an ensemble, their understanding of voicing and harmony, and appreciation of world music were all investigated through both the perceptions of the students as well as the instructors. Other areas investigated were the role of the instructor to determine how their teaching methods and topics covered impacted the students' opinion of the ensemble. This includes, but is not limited to, time spent teaching improvisation, rote teaching versus Western notation, and adding historical context by teaching the students the history of the ensemble. The Midwest region was chosen both for its high density of collegiate steel pan ensembles as well as its encompassing of some of the oldest pan ensembles in the U.S. The study used an explanatory mixed methodology employing two surveys, a student version and an instructor version, distributed to the collegiate steel pan ensembles of the Midwest via the internet. The researcher intends for the current data to serve the music community in several ways: first, by determining exactly what the students and instructors value about the ensemble, we will better understand how an instrument created less than a century ago was able to infiltrate music programs all over the world. Second, giving instructors insight on the students' perspectives will also enable them to create a more effective and enjoyable curriculum. And lastly, with this information, instructors and program supervisors will be better suited to determine just how large of a role the ensemble should play in their students' education.
Keywords: Steel pan; Drum curriculum; College education; Fine Arts (0357); Music (0413); Music Education (0522)